DOES GENDER EQUALITY IMPACT REGIONAL ECONOMIC GROWTH?: - Mudzakir, Aditya Muhammad; Rahmadini, Shintia (ipdn, 2024)
This research aims to examine the impact of gender equality on regional development, represented by regional economic growth. The analysis applies econometric methods to panel data from 27 districts/cities in West Java Province for the 2018–2022 period, with the Common Effect Model (CEM) selected as the optimal regression model for this study. Gender equality is represented by indicators such as the ratio of female to male in per capita expenditure, mean years of schooling, life expectancy, and labor force participation rate. The findings reveal heterogeneous effects: gender equality in per capita expenditure, education, and health positively influences economic growth, with health, as measured by life expectancy, being the most significant factor. Conversely, the labor force participation rate exhibits a negative effect, indicating challenges in optimizing female's roles in the labor market. Overall, the study finds that gender equality development contributes 12.34% to West Java's economic growth. These findings highlight the need to provide equal opportunities for female by enhancing access to education, healthcare, and economic resources while addressing barriers in labor force participation to achieve inclusive and sustainable development.Keywords: Econometrics Analysis, Economic Growth, Gender Equality, Regional Development.